Implementation of the Course Review Horay Learning Model to Improve Learning Outcomes in Islamic Education at SD Muhammadiyah 6 Surabaya - Sara Fitri Ramdhanis; Khozin Khozin; Busahdiar Busahdiar (Ar-Fachruddin: Pendidikan Agama Islam, 2024)
Research Objective– This study aims to evaluate the implementation of the course review horay learning model in improving the learning outcomes of Islamic education for first-grade students at SD Muhammadiyah 6 Surabaya. Method– The research employed classroom action research conducted in two cycles. Each cycle consisted of planning, action implementation, observation, and reflection stages. The subjects were first-grade students, while the objects were the learning process and outcomes using the course review horay model. Findings– The results showed an improvement in students' learning outcomes. In the initial condition before the action, the achievement rate was 60%. In the first cycle, it decreased to 50.5%, but then significantly increased in the second cycle to 82.5%, reflecting an improvement of 32%. The application of this model effectively enhanced students' learning outcomes, especially in the cognitive aspect. Implications/Limitations– The implementation of this model successfully created a more interactive and enjoyable learning atmosphere. However, the study is limited to first-grade students in one school and has not tested its effectiveness in other levels or subjects. Originality/Value– This study provides practical contributions to cooperative learning methods in Islamic education. The use of the course review horay model offers an innovative approach that integrates interactive elements to enhance students' learning outcomes.